Relocation of Dodecaseta McCammon & Stull, 1978 (Annelida, Capitellidae) in Notodasus Fauchald, 1972 - García Garza, María Elena; De León González, Jesús Ángel; Harris, Leslie H. (2017)
The capitellid polychaete genus Dodecaseta McCammon & Stull, 1978 is relocated in Notodasus Fauchald, 1972. Two species are redescribed based on examination of type material and three new combinations are proposed: Notodasus oraria (McCammon & Stull, 1978), N. eibyejacobseni (Green, 2002). N. fauchaldi (Green, 2002). N. kristiani (García-Garza et al., 2009), is synonymized under N. oraria. Some comments on Dasybranchus lumbricoides Grube, 1878 are included